2016
DOI: 10.1155/2016/7285132
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Measurement of Ocular Surface Temperature in Dry Eyes

Abstract: Purpose. To study ocular surface temperature (OST) in dry eyes by static and dynamic measures. Methods. OST was recorded on 62 dry eyes and 63 age- and sex-matched controls. Static measures were study of absolute OST at t = 0, 5, and 10 s after eye opening. Dynamic measures were study of mean change and net change in OST over 10 s of sustained eye opening. Ten OST indices studied were temperatures of the geometric center of the cornea (GCC), extreme temporal (T1) and nasal conjunctiva (T4), midtemporal (CT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…139 Evaporation causes the tear film to cool and is probably the main source of cooling in evaporative dry eye. 28,140 In those studies, subjects closed their eyes for 3–5 sec to warm the cornea, and then opened them for a 10-second recording. In that interval, the central corneal temperature fell significantly more in dry eye patients than in normals.…”
Section: Images Of Breakup Obtained By Different Methodsmentioning
confidence: 99%
“…139 Evaporation causes the tear film to cool and is probably the main source of cooling in evaporative dry eye. 28,140 In those studies, subjects closed their eyes for 3–5 sec to warm the cornea, and then opened them for a 10-second recording. In that interval, the central corneal temperature fell significantly more in dry eye patients than in normals.…”
Section: Images Of Breakup Obtained By Different Methodsmentioning
confidence: 99%
“…Mathematical as well as experimental studies have established that there is a posterior to anterior temperature gradient in the eye, with temperature close to core body temperature at the retina and approximately 2.5°C lower near the lens 2,3 . Currently, infrared cameras can be mounted on slit lamps and surface temperature of the eye can be readily mapped, with reported ocular surface temperatures of 32–35°C 4,5 . These studies have established the importance of the tear film in adding warmth to the eye surface; surface temperature dissipates by 1°C 10 s after blinking.…”
Section: Introductionmentioning
confidence: 98%
“…2,3 Currently, infrared cameras can be mounted on slit lamps and surface temperature of the eye can be readily mapped, with reported ocular surface temperatures of 32-35°C. 4,5 These studies have established the importance of the tear film in adding warmth to the eye surface; surface temperature dissipates by 1°C 10 s after blinking. Eye temperatures are lower in dry eye 5 and elevated in conditions such as Graves' ophthalmopathy 4 and decrease with treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corneal temperature values of 34 C and above were reported multiple times in literature, in particular as a target threshold for diagnostic purposes. 1,4,17,27,34 Other studies 1,6,49 reported that temperatures in the range 32.0-33.5 C were found across the corneal area. The hysteresis of the sensor was evaluated by temperature swing in the range 33.0 C to 38.0 C, and from 32.0 C to 33.0 C, with a stabilization time of 10 minutes at each 1.0 C step, showing average variations of z8 nm between advancing and receding measurements.…”
Section: Discussionmentioning
confidence: 93%